Ultra-high field 1H magnetic resonance imaging approaches for acute hypoxia. (October 2013) - Nielsen, Thomas; Nielsen, Niels Chr.; Holm, Thomas H.; Østergaard, Leif; Horsman, Michael R.; Busk, Morten
Abstract Background. Currently, radiation treatments are being optimised based on in vivo imaging of radioresistant, hypoxic tumour areas. This study aimed at detecting nicotinamide's reduction of acute hypoxia in a mouse tumour model by two clinically relevant magnetic resonance imaging (MRI) methods at ultra-high magnetic field strength. Material and methods. The C3H mammary carcinoma was grown to 200 mm3 in the right rear foot of CDF1 mice. The mice were anaesthetised with ketamine and xylazine prior to imaging. A treatment group received nicotinamide intraperitoneally (i.p.) at the dose 1000 mg/kg, and a control group received saline. MRI was performed at 16.4 T with a spatial resolution of 0.156 × 0.156 × 0.5 mm3. The imaging protocol included BOLD imaging and two DCE-MRI scans. Initial area under the curve (IAUC) and the parameters from the extended Toft's model were estimated from the DCE-MRI data. Tumour median values of 1) T2* mean, 2) T2* standard deviation, 3) DCE-MRI parameters, and 4) DCE-MRI parameter differences between scans were compared between the treatment groups using Student's t-test (significance level p < 0.05). Results. Parametric maps showed intra- and inter-tumour heterogeneity. Blood volume was significantly larger in the nicotinamide-treated group, and also the blood volume difference between the two DCE-MRI scans was significantly larger in the treatment group. Conclusion. Higher blood volume and blood volume variation was observed by DCE-MRI in the treatment group. Other DCE-MRI parameters showed no significant differences, and the higher blood volume was not detected by BOLD MRI. The higher blood volume variation seen with DCE-MRI may be influenced by the drug effect reducing over time, and furthermore the anaesthesia may play an important role.